Dual-emitting ZIF-8⊃4-MU@Zn2GeO4:Mn2+ nanocomposites for ratiomertic luminescent thermometer and information encryption. (September 2022) - Yi, Zishuo; Huang, Weiling; Xu, Yan
Abstract: Dual-emitting ratiometric optical thermometers with the advantages of excellent self-calibration and high-sensitivity have become a research hot spot. Herein, a dual-emissive 4-methylumbelliferone encapsulated ZIF-8 (ZIF-8⊃4-MU) modified Zn2 GeO4 :Mn 2+ nanocomposite was simply prepared by adding Zn2 GeO4 :Mn 2+ nanorods into a methanol solution containing 4-methylumbelliferone (4-MU), zinc (II) nitrate hexahydrate, and 2-methylimidazole. Accompanying with the self-assembly of ZIF-8⊃4-MU, the binding affinity of Zn 2+ ions to the surface of Zn2 GeO4 :Mn 2+ nanorods enables the formation of ZIF-8⊃4-MU@Zn2 GeO4 :Mn 2+ nanocomposite. The photoluminescence violet-blue (420 nm) and green emissions (531 nm) of the nanocomposite can be ascribed to the two independent luminescent centers of 4-MU dyes confined in ZIF-8 and the characteristic transition of 4 T1 - 6 A1 for Mn 2+ ions doped in Zn2 GeO4, respectively. The fluorescent intensity ratios (FIRs) of 4-MU to Mn 2+ (I420 nm /I531 nm ) showed excellent self-calibrating temperature monitoring functions with a maximum relative sensitivity (Sr ) of 1.82%· o C −1 and stable reusability in the temperature range of 20–100 °C. Also, the ZIF-8⊃4-MU@Zn2 GeO4 :Mn 2+ hybridized polyvinyl alcohol (PVA) transparent film showed a similar multi-emitting behavior, as well as good processability and tensile properties. Benefiting from the excitation-dependent emitting property of ZIF-8⊃4-MU@Zn2 GeO4 :Mn 2+, a multiple optical encryption of digital information was successfully realized based on a two-dimensional code, achieving an enhanced security level for preventing counterfeiting. This proof-of-concept study offers a feasible assembled way in fabricating multi-mode luminescent nanocomposites for ratiometric temperature sensing and information encryption. Graphical abstract: Image 1 Highlights: A dual-emitting ZIF-8⊃4-MU@Zn2 GeO4 :Mn 2+ nanocomposite was simply self-assembled. It exhibited self-calibrated ratiometric luminescent temperature sensing performances. The integrated transparent and flexible PVA film had multi-color emitting property. Its excitation-dependent multi-color emissions can be used for information encryption.